Correlation of time-different ground radiometry datasets on an example of fault survey (Hradište border fault, Turiec Basin, Western Carpathians, Slovakia) - MOJZEŠ, Andrej (Contributions to Geophysics and Geodesy, 2025)
Complex geophysical survey (seismic tomography, electrical resistivity tomography and electromagnetic interference measurement, spontaneous potential, ground penetration radar, gravimetry, magnetometry and radiometry) was carried out along 450 m-long profile crossing the assumed map track line of the Hradište border fault to specify its position and some of its features. As a result, a 115 m-wide fault zone was identified, vertically or steeply dipped to the south-east and east. Because of incompatibilities between the results of deep-range geophysical methods (seismics, geo-electrics, gravimetry and magnetometry) and the results of shallow-range radiometric methods (ground gamma-ray spectrometry and soil radon emanometry), the latter were measured twice, in 2012 and 2016 years. The comparison of results of both radiometric measurements shows an acceptable level of linear correlation mainly for thorium concentration (R = 0.87), gamma dose rate (R = 0.84), radon activity concentration (R = 0.69) and potassium concentration (R = 0.66), but very low one for uranium concentration (R = 0.12). Alongside, no correlation between soil uranium concentration and activity concentration of radon in soil air was determined. These results confirm the behaviour of measured radiometric quantities in soils and weathered rock covers, and strong influenceability mainly of uranium and radon presence in shallow subsurface horizon by changing meteorological conditions.